In vivo generation of collagen specific Tregs with AAV8 suppresses autoimmune responses and arthritis in DBA1 mice through IL10 production - Matthew Wade (Nature Portfolio, 2021)
Abstract Available therapeutics for autoimmune disorders focused on mitigating symptoms, rather than treating the cause of the disorder. A novel approach using adeno-associated virus (AAV) could restore tolerance to the autoimmune targets and provide a permanent treatment for autoimmune diseases. Here, we evaluated the ability of collagen II T-cell epitopes packaged in adeno-associated virus serotype 8 (AAV-8) vectors to reduce pathogenic cellular and humoral responses against collagen and to mitigate the disease in the collagen-induced arthritis mouse model. The cytokines and immune cells involved in the immune suppression were also investigated. Mice treated with AAV-8 containing collagen II T-cell epitopes demonstrated a significant reduction in the arthritis symptoms, pathogenic collagen specific antibody and T cell responses. The AAV-8 mediated immune suppression was mediated by increased interleukin-10 expression and regulatory T cells expansion. Altogether, this study strengthens the notion that AAV vectors are promising candidates for the treatment of autoimmune diseases.